Basidiomycete pigments as sustainable food colorants and stabilizers: from fungal biology to industrial potential - Karunarathna, Samantha C.; Tibpromma, Saowaluck; Lu, Wenhua; Perera, Hansika; Tarafder, Entaj; Karunarathna, Baggya Sharmali; Dai, Dong-qing; Kumla, Jaturong; Karunanayake, Chathurika; Hapuarachchi, Kalani Kanchana; Suwannarach, Nakarin (Frontiers in Microbiology, 2025)
Pigmented Basidiomycete fungi are emerging as multifunctional and environmentally friendly substitutes to man-made food coloring. In addition to their bright colors, pigments from these fungi, including melanin, pulvini acids, carotenoids, and phenoxazines, also exhibit potent antioxidant, anti-microbial, and even potential therapeutic effects. Fungal pigments offer greater stability under processing conditions compared to those of plant origin and can be cost-effectively produced by biotechnological culture, particularly agro-waste-based fermentation systems. This review provides an overview of the chemical diversity, biosynthesis, and extraction of pigments from food and non-food Basidiomycetes such as the genera Cantharellus, Pycnoporus, Boletus, Pleurotus, and others. Particular emphasis is on their applications in the food and nutraceutical industries, challenges in scaling up and regulatory aspects, and future prospects of fungal biotechnology as a renewably available source of natural pigments.